Marias : biopolítica, vida nua e resiliência - Badiali, Michelle Ferret (2009)
Taking the narrative of life of three women (homeless), Maria José (residente of a psychiatric hospital) and Maria de La Luz Cervantes (fictional character of Gabriel Garcia Marquez, accidentally intern in a psychiatric hospital), the dissertation "Marias: Biopolitics, bare life and their stories" brings Giorgio Agamben's theories referring to Naked Life and Homo Sacer, Michel Foucault's with the biopolitics and resiliences written by Boris Cyrulnik. Its on these three women life stories that the dissertation develops a imaginary concentration camp to work their lives and bodies subjection to the external power, the biopolitic